Healthcare‐professional patients' conceptions of being ill and hospitalised – a phenomenographic study. Issue 11 (10th March 2017) - Prenkert, Malin; Carlsson, Eva; Svantesson, Mia; Anderzén‐Carlsson, Agneta
Abstract : Aims and objectives: To describe the variation of conceptions of being ill and hospitalised, from the perspective of healthcare‐professional patients. Background: Previous literature focuses on either physicians' or nurses' experiences of being a patient, without aiming at determining a variation of ways of understanding that phenomena. Nor have we been able to identify any study reporting other healthcare professionals' experiences. Design: This study has an inductive descriptive design. Methods: Qualitative interviews with healthcare professionals ( n = 16), who had been hospitalised for at least two days. Phenomenographic data analysis was conducted. Results: The feelings of security were based on knowledge, insight and trust, and acceptance of the healthcare system. Being exposed and totally dependent due to illness provoked feelings of vulnerability and insecurity. The patients used their knowledge to achieve participation in the care. The more severe they perceived their illness to be, the less they wanted to participate and the more they expressed a need for being allowed to surrender control. The patients' ideal picture of care was sometimes disrupted, and based on their experience, they criticised care and made suggestions that could contribute to general care improvements. Conclusions: Healthcare‐professional patients have various conceptions of being ill and hospitalised. Based on the general nature of the many needs expressed, we believe that the insights provided in this study can be transferred so as to also be valid for lay patients. Possibly, an overhaul of routines for discharge planning and follow‐up, and adopting a person‐centred approach to care, can resolve some of the identified shortcomings. Relevance to clinical practice: The results can be used for the purpose of developing knowledge for healthcare professions and for educational purposes.